Estimation of Uranium Concentration in Urine Samples of Kidneys Failure Patients in Al- Muthanna Governorate - Abed, Muayad M.; Mahdi, Khalid H.; AL Hamadany, Weam S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The measurement of uranium concentration in human urine is very important in assessment of occupational and public exposure to uranium. In the present work, the fission track technique was used to decide uranium concentration in blood of Kidneys Failure Patients in Al- Muthanna Governorate. The uranium concentration values in urine samples of Kidneys Failure Patients ranged between 0.92  to 4.87  , while Healthy group results were ranged 0.91  to 1.82 . Results showed that the concentration of uranium in the URINE increases in kidney failure patients